Faktor Faktor yang Mempengarui Gangguan Pendengaran pada Lansia: Analisis Perspektif Pasien dan Keluarga - Piona Selsilia; Intan Ramadani; Lena Marianti; Cindya Elisa; Alim Firmansyah (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Hearing loss in the elderly is a common health problem that can affect quality of life, including family perspectives and patient care. The purpose of this study was to identify risk factors that cause hearing loss in the elderly and to analyze patient and family perceptions of the impact of hearing loss. The method used in this study was a qualitative approach through the library research method. The data obtained were analyzed using thematic analysis techniques. The study showed that the main risk factors for hearing loss in the elderly are advanced age, noise exposure, hypertension, diabetes, and use of ototoxic drugs. Family involvement in the care process can improve patient autonomy and quality of care. In addition, communication challenges between families and health care providers also play an important role in the effectiveness of hearing loss management. In addition, patient and family perceptions of hearing loss are often influenced by limited understanding of hearing loss and lack of awareness of the importance of early detection. Most families support patients, but hearing loss causes communication difficulties that cannot be treated immediately. This study shows the need for a holistic approach to treating hearing loss in the elderly, including patient and family education and increasing early detection by health care professionals.